Ghrelin in Health and Disease - Smith, Roy G.; Thorner, Michael O.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Ghrelin, the endogenous ligand for the growth hormone secretagogue (GHS) receptor, is critical in the control of food intake and energy balance. The ghrelin receptors are now known to have important physiological properties as modulators of growth hormone release, appetite, glucose homeostasis, metabolism, immune function, neurotransmitter activity, cognitive function and neurodegeneration. Bringing all of this information together in the first comprehensive text on the topic, Ghrelin in Health and Disease provides a state-of-the-art synthesis of the latest work in this area for physicians and physician-scientists. This volume addresses the unique property of ghrelin as a modulator of function. Such a property provides potential utility for safe intervention in a wide variety of disease states. Indeed as we learn more about the basic physiology of ghrelin, the potential for treating new disease targets emerge requiring validation in the clinic. Each chapter in this volume is authored by a leading investigator in the field. The introductory chapter sets the background for the book and provides a superb overview of the relevance of ghrelin to physiology, describing how the discovery of ghrelin has prompted us to completely rethink traditional physiology. The authors conclude their chapters by critically addressing the future translational aspects of ghrelin biology and outlining what key basic research and clinical questions remain to be addressed. An invaluable resource, Ghrelin in Health and Disease distinguishes itself as the first comprehensive title covering all of the molecular and clinical issues relating to ghrelin and advancing our clinical understanding of obesity, growth, and reproductive pathogenesis.
Ghrelin: A History of Its Discovery -- Enzymatic Processing of Ghrelin Precursor -- Ghrelin’s Novel Signaling in Islet b-Cells to Inhibit Insulin Secretion and Its Blockade As a Promising Strategy to Treat Type 2 Diabetes -- Gastric Ghrelin in the Regulation of Appetite and Metabolism -- Ghrelin Regulation of AMPK in the Hypothalamus and Peripheral Tissues -- Ghrelin: Neuropeptide Regulator of Metabolism.-GOAT and the Regulation of Energy and Glucose Homeostasis.- Ghrelin Regulation of Sleep, Circadian Clock and Body Temperature -- Ghrelin Regulation of Learning, Memory and Neurodegeneration.-Ghrelin Antagonism: A Potential Therapeutic Target for Addictive Behavior Disorders.-Ghrelin Receptor Agonists in Cachexia of Human Aging -- Use of Ghrelin and Ghrelin Receptor Agonists in Cancer- and Chemotherapy-Induced Cachexia -- Ghrelin in Cachexia Associated with End-Stage Renal Disease -- Ghrelin Suppression of Autoimmune Encephalomyelitis.-  Physiological Roles of Des-Acyl Ghrelin.                           .
Keywords: Endocrinology .; Geriatrics; Immunology; Neurosciences; Nutrition .; Endocrinology; Geriatrics/Gerontology.; Immunology; Neurosciences; Nutrition